PENANAMAN MODAL ASING PT. INDOFOOD KE KENYA TAHUN 2014-2024 - Dewi, Sari Amalia; Wibowo, Shabrina Ramadhanti (Moestopo Journal of International Relations (MJIR), 2024)
This study aims to analyze how foreign direct investment by PT. Indofood in conducting outward investment by establishing factories and Indofood's achievements from 2014 to 2024. The theory and concept used are foreign investment and multinational company. The result of this research is that foreign investment made by PT Indofood experienced the popularity of Indomie in Kenya in selling Indomie products and strengthening cooperation between Indonesia and Kenya in other sectors. In conducting foreign direct investment, Indonesia with the company name PT. Indofood opens employment opportunities and transfers modern technology.